ENERGY MANAGEMENT SOFTWARE FOR STUDENTS IN ENGINEERING EDUCATION - (:unkn) unknown (My University, 2020)
Energy demand of a country should be particularly supplied by indigenous_x000D_ energy sources; otherwise, the country would become an energy importing_x000D_ country and dependent on energy-rich countries. In order to benefit from the_x000D_ current renewable energy resources efficiently, many engineers who are_x000D_ specialized on energy management (economic, planning, organization and_x000D_ optimization) are strongly required to be educated with the support of today’s_x000D_ advance technology. In this context, various engineering disciplines_x000D_ associated with the concept of energy have been established in many_x000D_ universities around the world as well as in Turkey. In this study, Hybrid_x000D_ Optimization of Multiple Energy Resources (HOMER) software which is very_x000D_ useful for modeling renewable and conventional technologies in various_x000D_ energy management applications and also easy to use, is introduced in detail_x000D_ and presented to today’s and future’s energy engineers. In order to better_x000D_ understand how the HOMER is efficiently applied, a real-time application for_x000D_ Marmara University Technical Education Faculty which was discussed and_x000D_ is presented in detail.